Analysis of Successful Acquisition of PT Siloam International Hospital Tbk in the Indonesia Stock Exchange - Rossherleen Clarissa Halim (Budapest International Research and Critics University, 2023)
The acquisition was made by PT Siloam International Hospitals TBK on the Indonesia Stock Exchange (IDX). The value obtained after selecting the acquisition will be greater than the total value before making the acquisition. Another advantage given to companies that choose to acquire their companies is the increased ability in the fields of marketing, research, managerial skills, technology transfer, and efficiency of the company. The research method used is a literature review method with the help of document data collection techniques. The results showed that the acquisition decision made by the company with the intention of being a means of developing financial performance was declared not achieved based on the profitability ratio.